43.1k views
0 votes
Solve the quadratic equation (2x-3)^2 = 6(3-2x)

User Zoka
by
5.3k points

1 Answer

3 votes

Answer:


x=(3√(2)-3 )/(2)


x=-(3√(2)-3 )/(2)

Explanation:

Open the brackets first:


4x^2+9=18-12x

Simplify:


4x^2+12x-9=0

It is determined that this can't be factored, so rewrite the equation so you can complete the square.


x^2+3x=(9)/(4)

Take the square of 1.5 and add it to both sides:


x^2 + 3x+ (9)/(4) =\frac{9}4} +(9)/(4)

Factor:


(x+(3)/(2))^2=(9)/(2)


x+(3)/(2) = (3√(2) )/(2 )

or
x+(3)/(2) =-(3√(2) )/(2)

So
x=(3√(2)-3 )/(2)

or
x=-(3√(2)-3 )/(2)

User Sina Amirshekari
by
5.8k points